A method for developing mobile virtual laboratories - Zervas, P.; Kalimeris, I.; Sampson, Demetrios (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 IEEE. Virtual laboratories offer access to virtual science experiments and they are recognized as pedagogically effective in increasing students' interest in science, as well as students' motivation and engagement. Moreover, the proliferation of mobile devices has created a growing trend for developing mobile virtual labs. However, the process of designing and developing such mobile apps should be based on specific guidelines towards addressing the technical restrictions of mobile devices and improving end-user experience. Existing guidelines that aim to facilitate this process are the App Quality Alliance (AQuA) guidelines. In this paper, we identify common functionalities of existing mobile virtual labs and we exploit AQuA guidelines towards proposing a method for developing mobile virtual labs. Additionally, we apply this method for developing a mobile virtual lab, namely ASK Mobile Virtual Laboratory (ASK-MVL) and we perform an initial evaluation in terms of user experience.